The moderating role of gender in the relationship between religiosity, social support and academic stress among mahasantri in Yogyakarta - Novandrila, Regita Nisa; Uyun, Qurotul (Psikis : Jurnal Psikologi Islami, 2025)
This study aims to examine the relationship between religiosity and social support with academic stress among mahasantri in Yogyakarta. Mahasantri are university students who reside in Islamic boarding schools and undertake dual responsibilities in both academic activities at the university and religious activities at the pesantren. The research involved 206 active mahasantri and the instruments used in this study included the Perception of Academic Stress Scale (PASS), the Centrality of Religiosity Scale (CRS-15), and the Multidimensional Scale of Perceived Social Support (MSPSS). Regression analysis results indicated a negative relationship between religiosity and academic stress (ρ < .001). The correlation analysis showed a negative relationship between religiosity and academic stress (ρ < .001), as well as between social support and academic stress (ρ = .010). Religiosity and social support contributed significantly to the reduction of academic stress among mahasantri in Yogyakarta (ρ <.001), with a total contribution of 7.96%. These findings demonstrated that the higher the levels of religiosity and social support possessed by mahasantri, the lower their levels of academic stress. The moderated regression analysis showed that gender did not significantly moderate the relationships between religiosity and academic stress, nor between social support and academic stress (ρ > .050). These findings indicated that the effects of religiosity and social support on academic stress are consistent across both male and female mahasantri.The results implied that strengthening religiosity and social support can serve as protective factors against academic stress, thereby universities and pesantren have to provide supportive and faith-based programs for mahasantri.